Estudo estrutural e morfológico do óxido de zinco preparado pelo método hidrotérmico - Marinho, Juliane Zacour (2013)
In this work were prepared zinc oxide (ZnO) samples by microwave - hydrothermal (MH) method and realized a structural analysis and morphology of the samples assessing the effect of different experimental parameters used: heating method, synthesis temperature, reaction time, heating rate and addition of surfactants. The samples were characterized structurally by the techniques of X-ray diffraction (XRD) and Raman spectroscopy. The particle size and morphology were investigated by scanning electron microscopy by field emission (FEG-SEM). The optical properties were analyzed by photoluminescence spectroscopy (PL). The results of XRD showed the formation of crystalline structures related to ZnO wurtzite phase, indicating a periodic structural organization at long range. The Raman active modes that characterize the hexagonal structure of ZnO were observed and the presence of structural defects showed the short-range influence on the optical properties of the obtained materials. Samples showed photoluminescent properties with maximum emission in the green region of the visible spectrum, which is related to structural defects in the medium and short ranges, the oxygen vacancies, Zn2+ interstitials in the ZnO crystal lattice, which are types of defects that can be generated during the synthesis process. The addition of urea synthesis led to the formation of nanoparticles rounded and more uniform than the samples obtained in presence of polyethylene glycol. The materials prepared in this work have potential application in optical devices, catalysis, gas sensors and solar cells.